Compact polar moieties induce lipid-water systems to form discontinuous reverse micellar phase - Kumar, Manoj; Patil, Naganath G.; Choudhury, Chandan Kumar; Roy, Sudip; Ambade, Ashootosh V.; Kumaraswamy, Guruswamy (Soft Matter, 2015)
The role of molecular interactions in governing lipid mesophase organization is of fundamental interest and has technological implications. Herein, we describe an unusual pathway for monoolein/water reorganization from a bicontinuous mesophase to a discontinuous reverse micellar assembly, directed by the inclusion of polar macromolecules. This pathway is very different from those reported earlier, wherein the Fd3m phase formed only upon addition of apolar oils. Experiments and molecular dynamics simulations indicate that hydrophilic ternary additives capable of inducing discontinuous phase formation must (i) interact strongly with the monoolein head group and (ii) have a compact molecular architecture. We present a detailed investigation that contrasts a monoolein-water system containing polyamidoamine (PAMAM) dendrons with one containing their linear analogs. The Fd3m phase forms only on the addition of PAMAM dendrons but not their linear analogs. Thus, the dendritic architecture of PAMAM plays an important role in determining lipid mesophase behavior. Both dendrons and their linear analogs interact strongly with monoolein through their amine groups. However, while linear polymers adsorb and spread on monoolein, dendrons form aggregates that interact with the lipid. Dendrons induce formation of an intermediate reverse hexagonal phase, which subsequently restructures into the Fd3m phase. Finally, we demonstrate that other additives with compact structures that are known to interact with monoolein, such as branched polyethylenimine and polyhedral silsesquioxane cages, also induce the formation of the Fd3m phase.

Controlled micellar disassembly of photo- and pH-cleavable linear-dendritic block copolymers - Kalva, Nagendra; Parekh, Nimisha; Ambade, Ashootosh V. (Polymer Chemistry, 2015)
A linear-dendritic block copolymer with both photo-and pH-cleavable linkages at the junction between the hydrophobic dendron and hydrophilic linear polymer was synthesised. The photocleavable o-nitrobenzyl group attached to alkyne was introduced at the focal point of polyester dendron and acid-degradable acetal linkage with terminal azide was introduced at one end of linear polyethylene glycol. The two segments were connected using click chemistry. The copolymer was found to self-assemble into micelle-like aggregates in dilute aqueous solution. Stimuli-responsive disassembly of the aggregates was studied by monitoring fluorescence emission of the encapsulated hydrophobic dye and dynamic light scattering (DLS). Products of acetal cleavage at acidic pH were analyzed by gel permeation chromatography and NMR spectroscopy. The photo and pH stimuli were applied separately as well as simultaneously to study the rate of dye release. The synergistic effect of the two stimuli on dye release was demonstrated and the non-cytotoxic nature of the polymer was shown using the MTT assay. Cell uptake of DOX-loaded micelles and photo-induced release of the drug resulting in significantly higher cytotoxicity than by free DOX was demonstrated using MDA-MB-231 cells.

Copper and silver nanoparticles stabilized by bistriazole-based dendritic amphiphile micelles for 4-nitrophenol reduction - Patil, Naganath G.; Basutkar, Nitin B.; Ambade, Ashootosh V. (New Journal of Chemistry, 2017)
Copper and silver nanoparticles were fabricated in aqueous solution using micellar assemblies of dendritic amphiphiles containing triazole rings. Dendritic amphiphiles displaying a bistriazole unit between a hydrophobic benzyl ether dendron and two oligo(ethylene glycol) (OEG) chains were synthesized using click chemistry. Micelles were characterized by DLS, TEM, CMC determination, and dye encapsulation. Micellar size was dependent on the dendron backbone structure and OEG chain length. Metal nanoparticles were characterized by TEM and UV-Vis spectroscopy. The Cu NPs had a smaller average particle diameter than the Ag NPs. The micelle-stabilized nanoparticles, at a concentration of 7.5 ppm, were shown to efficiently catalyze the reduction of 4-nitrophenol to 4-aminophenol in the presence of NaBH4 in aqueous solution without stirring, using up to 1 ppm of substrate. The reaction catalyzed by Cu NPs followed zero order kinetics (k = 3.48 x 10(-3) M s(-1)), while the Ag NP-catalyzed reaction followed pseudo-first order kinetics (k = 1.28 x 10(-3) s(-1)).

Catechol- and phenolic hydroxyl-functionalized partially bio-based (Co) poly(ether sulfone)s with multifarious applicability - Wale, Apparav K.; Jagtap, Ashish S.; Pandey, Priyanshi R.; Dastager, Syed G.; Shelke, Manjusha V.; Ambade, Ashootosh V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2024)
A largely bio-based new bisphenol, namely, 4,4 `-((3,4-dimethoxyphenyl)methylene)-bis(2-methoxyphenol) (DMBM) was synthesized by the reaction of veratraldehyde with guaiacol. DMBM and varying compositions of DMBM and bisphenol A were polycondensed with bis(4-fluorophenyl) sulfone to afford reasonably high molecular weight film-forming (co)poly(ether sulfone)s possessing built-in methoxyl groups. T10 and Tg values of (co)poly(ether sulfone)s were in the range 382-478 degrees C and 171-187 degrees C, respectively indicating their good thermal stability and the values decreased with increase in mol % incorporation of DMBM. The methoxyl groups present in (co)poly (ether sulfone)s were quantitatively de-blocked resulting in the formation of corresponding polymers possessing pendant catechol moieties and free phenolic hydroxyl groups. By virtue of the presence of these functional moieties, (co)poly(ether sulfone)s are amenable for post-polymerization modifications, and exhibited properties such as antimicrobial (23 mm against Staphylococcus aureus and 18 mm against Escherichia coli)), antioxidant (72 % scavenger of free radicals), adhesive (2.24 MPa lap shear strength) and usefulness as redox-active agent in zinc-ion batteries. These data underscore the promise of DMBM as a versatile monomer of wider utility for the synthesis of functional (co)poly(ether sulfone)s capable of expanding their applicability beyond the conventional ones.
Keywords: (Co)poly(ether sulfone)s; adhesive; Antimicrobial; Antioxidant; bio-based; bisphenol; Zinc-ion batteries